Relation Between Plasma Proteomics Analysis and Major Adverse Cardiovascular Events in Patients With Stable Coronary Artery Disease - Dregoesc, Mihaela Ioana; Ţigu, Adrian Bogdan; Bekkering, Siroon; van der Heijden, Charlotte D. C. C.; Bolboacǎ, Sorana Daniela; Joosten, Leo A. B.; Visseren, Frank L. J.; Netea, Mihai G.; Riksen, Niels P.; Iancu, Adrian Corneliu (Frontiers in Cardiovascular Medicine, 2022)
Objective: Despite the advances in the control of traditional risk factors, coronary artery disease (CAD) remains the greatest cause of morbidity and mortality. Our aim was to establish the relation between plasma proteomics analysis and the risk of cardiovascular events in patients with stable CAD. Materials and Methods: Patients with stable CAD and documented coronary atherosclerosis were screened for inclusion. Using proximity extension assays, 177 plasma proteins were simultaneously measured. The endpoint consisted of the first major adverse cardiovascular event (MACE) and was the composite of cardiovascular death, acute coronary syndrome, stroke, transient ischemic attack, or acute limb ischemia at 18 months follow-up. Cox proportional-hazards regression with adjustment for multiple comparisons was used to identify biomarkers for the outcomes of interest. Results: The cohort consisted of 229 patients. Six mediators were associated with MACE (p<0.001). For these markers, the risk of MACE was calculated: tumor necrosis factor receptor superfamily member 13B (HR 1.65; 95%CI 1.30‒2.10), C-C motif chemokine-3 (HR 1.57; 95%CI 1.23‒1.98), decorin (HR 1.65; 95%CI 1.26‒2.16), fibroblast growth factor-23 (HR 1.56; 95%CI 1.23‒1.99), tumor necrosis factor-related apoptosis-inducing ligand-receptor 2 (TRAIL-R2) (HR 1.61; 95%CI 1.23‒2.11), and tumor necrosis factor receptor superfamily member 10A (HR 1.69; 95%CI 1.25‒2.29). Except for TRAIL-R2, the other mediators were associated with MACE independent of age, sex, diabetes mellitus, or estimated glomerular filtration rate. Conclusions: In patients with stable CAD, five novel biomarkers were identified as independent risk factors for adverse outcomes. Novel biomarkers could represent pharmacological targets for the prevention of adverse cardiovascular events.